Der fachübergreifende Unterricht in der bayerischen Hauptschule: Eine empirische Untersuchung zu Erfahrungen von Lehrern mit dem Fach Geschichte/Sozialkunde/Erdkunde (GSE) - Bauriegel, Gerd; Schrüfer, Gabriele (Zeitschrift für Geographiedidaktik (ZGD), 2006)
The study aimed at finding a correspondence between the pros and cons of multidisciplinary instruction as described in literature and the practical experiences of teachers. For this purpose 1060 teachers of Bavarian extended elementary schools teaching the combination of subjects history/social studies/geography were interviewed. The most important result is the fact that the disadvantages of multidisciplinary instruction as described in literature were clearly confirmed by the practical experience of the interviewed teachers.The following subjects were most frequently criticised:• a time budget too small to allow an expedient learning of methods, in particular reading a map• the fact that there is no connection between the individual curriculae, which would be necessary for multidisciplinary instruction• the unequal weighting which the individual subjects experience, by which particularly geography suffers• the fact, that the scientific, didactic and methodical competences of the teachers are restricted to one subject only.In contrast to this, advantages described in theoretical literature could hardly be confirmed. Especially two aspects were unequivocally assessed as positive, which are not conclusively a result of multidisciplinary instruction:• the fact that as a result of combining the three subjects pupils perceive the instruction as more varied• the abolition of the existing one-hour classes and the associated smaller number of achievement tests.